2007
DOI: 10.3758/bf03193600
|View full text |Cite
|
Sign up to set email alerts
|

Buffered forgetting: When targets and distractors are both forgotten

Abstract: In three experiments, we investigated prior findings that, following some memory tasks, essentially flat d or forced-choice retention curves are produced. These curves have been interpreted as indicating that forgetting is not present over the intervals examined; however, we propose in this article that forgetting is actually present whenever hit rates and false alarm rates are both declining, despite the result being a flat retention curve. We demonstrate that such curves can be produced using a pair recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This body of work has produced specific support for the assumption that the use of context with explicit but not implicit retrieval instructions is a major factor in the processes differentiating the effects of these instructions (Humphreys et al, 2000a(Humphreys et al, , 2000bTehan et al). It has also supported the idea of pre-access control processes (Humphreys et al, 2003;Weeks et al). Most importantly it has provided guidance in the design of the current set of experiments.…”
Section: Discussionmentioning
confidence: 77%
“…This body of work has produced specific support for the assumption that the use of context with explicit but not implicit retrieval instructions is a major factor in the processes differentiating the effects of these instructions (Humphreys et al, 2000a(Humphreys et al, , 2000bTehan et al). It has also supported the idea of pre-access control processes (Humphreys et al, 2003;Weeks et al). Most importantly it has provided guidance in the design of the current set of experiments.…”
Section: Discussionmentioning
confidence: 77%
“…He concluded that memory for word pairs is "more resistant to the effects of decay, interference from intervening events, or both" than is memory for single items (Hockley, 1992(Hockley, , p. 1328. However, Weeks, Humphreys, and Hockley (2007) later argued that Hockley's (1991Hockley's ( , 1992 finding of flat forgetting curves did not show a complete absence of forgetting, but instead suggested that interference was affecting targets and distractors in the same way. Nevertheless, it may be that there is no significant effect of list length when the stimuli are word pairs, simply because they are resistant to the influence of interference from other study pairs.…”
Section: Experiments 1: Word Pairsmentioning
confidence: 99%
“…Underwood found no build up of proactive interference when study participants were able to use category cues to support memory. Researchers have subsequently shown that when attempting to recall, for example, to a particular metal cue individuals use a representation of the context (e.g., the day the materials were learned) as an additional cue (Humphreys, Bain, & Pike, 1989; Weeks, Humphreys, & Hockley, 2007). When the contextual cue is similar across instances of learning (e.g., other days of study) there is proactive interference.…”
Section: Initial Sponsorship Exposurementioning
confidence: 99%